2020
DOI: 10.3390/cells9102224
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Leptin, the Leptin Receptor and FGFR1 in Primary Human Breast Tumors

Abstract: Obesity is associated with increased breast cancer risk and poorer cancer outcomes; however, the precise etiology of these observations has not been fully identified. Our previous research suggests that adipose tissue-derived fibroblast growth factor-2 (FGF2) promotes the malignant transformation of epithelial cells through the activation of fibroblast growth factor receptor-1 (FGFR1). FGF2 is increased in the context of obesity, and increased sera levels have been associated with endocrine-resistant breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Pathophysiological mechanisms remain unclear, but there are many factors involved in the association between obesity and BC, such as chronic subclinical inflammation, sex hormone deregulation, insulin/IGF-1 pathways, or the secretion of different adipokines like leptin [ 25 ]. Although some studies did not found association between leptin and BC [ 89 , 90 ], circulating leptin or its gene expression has been widely correlated with BC risk and progression, as well as proliferation and survival of BC cells [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Besides, leptin immunostaining has been proposed as a useful technique by supporting the identification of histotype, stage, grade, lymph node involvement, relapse, and prognosis in BC [ 101 ].…”
Section: Role Of Leptin As a Bad Actor In Cancermentioning
confidence: 99%
“…Pathophysiological mechanisms remain unclear, but there are many factors involved in the association between obesity and BC, such as chronic subclinical inflammation, sex hormone deregulation, insulin/IGF-1 pathways, or the secretion of different adipokines like leptin [ 25 ]. Although some studies did not found association between leptin and BC [ 89 , 90 ], circulating leptin or its gene expression has been widely correlated with BC risk and progression, as well as proliferation and survival of BC cells [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Besides, leptin immunostaining has been proposed as a useful technique by supporting the identification of histotype, stage, grade, lymph node involvement, relapse, and prognosis in BC [ 101 ].…”
Section: Role Of Leptin As a Bad Actor In Cancermentioning
confidence: 99%
“…In our study, the association of Ob-R with HER2+ and TN tumors is difficult to explain, given the contradictory data in the literature. However, without estrogen signaling, it is attractive to speculate with the concept that tumor progression may be driven by other signaling factors such as fibroblast growth factor receptor-1 (FGFR-1), insulin growth factor 1 (IGF-1), or Ob-R [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…With LEPR loss, cancer cells exhibited a less aggressive phenotype, and macrophage recruitment was abolished; the phagocytic activity and cytokine production of macrophages also appeared to decrease [ 56 ]. Cotreatment with leptin and adipose tissue-derived fibroblast growth factor-2 (FGF2) was reported to induce the malignant transformation of breast epithelial MCF-10A cells, and this effect was found to be attenuated by ruxolitinib and AG490, two separate inhibitors of Jak2, which is downstream of the leptin receptor, suggesting the critical interplay of leptin, leptin receptor and Jak2 in cancer progression [ 57 ]. The inhibitory effects of globular adiponectin on leptin-promoted inflammasome activation and tumor growth were further verified in breast MCF-7 cell and xenograft models via mechanisms including HO-1 induction and ER-α signaling modulation [ 58 ].…”
Section: Lep Somatic Mutations and Cancermentioning
confidence: 99%